IMPROVING KNOWLEDGE AND AWARENESS OF DENTAL AND ORAL HEALTH THROUGH AN EDUCATION PROGRAM FOR STUDENTS OF SDN DUWET 3 KEDIRI: PENINGKATAN PENGETAHUAN DAN KESADARAN KESEHATAN GIGI DAN MULUT MELALUI PROGRAM EDUKASI PADA SISWA SDN DUWET 3 KEDIRI - Mardiana Prasetyani Putri; Ningsih Dewi Sumaningrum; Khoirunissa Salsa N.P; Laura Dhea Hidayat; Nova Putri Anggraini; Oktarina Dewi Mutiasari; Siti Khoirun Nisa; Yolinda Margracia Y. Kette (WISDOM : Jurnal Pengabdian Kepada Masyarakat Wisdom, 2026)
Oral health is an important indicator of general health, yet the prevalence of dental caries among Indonesian children remains very high. This Community Service Program (CSP) aims to increase students’ awareness and knowledge at SDN Duwet 3 Kediri. Through outreach and education, this intervention is expected to instill healthy dental habits from an early age, thereby preventing future problems. The methods used included interactive lectures, toothbrushing demonstrations, and pre- and post-test-based evaluations. A total of 29 second- and third-grade students participated in this activity. Educational materials included an introduction to oral anatomy, types and functions of teeth, causes of caries, correct toothbrushing techniques, and nutrition for healthy teeth. Pre-test results showed a low level of students’ initial knowledge, with an average score of 48.96. After the intervention, the post-test score increased to 58.96. A paired statistical test showed this increase was significant (p=0.019), proving the effectiveness of the educational program. Furthermore, students showed strong enthusiasm for practicing and were committed to implementing healthy habits daily. These findings conclude that practice-based health education is effective in instilling healthy behaviors in elementary school children. Continuation of similar programs is highly recommended to strengthen the habit of maintaining dental and oral health from an early age.